2020
DOI: 10.1017/jog.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

Firn cold content evolution at nine sites on the Greenland ice sheet between 1998 and 2017

Abstract: Current sea-level rise partly stems from increased surface melting and meltwater runoff from the Greenland ice sheet. Multi-year snow, also known as firn, covers about 80% of the ice sheet and retains part of the surface meltwater. Since the firn cold content integrates its physical and thermal characteristics, it is a valuable tool for determining the meltwater-retention potential of firn. We use gap-filled climatological data from nine automatic weather stations in the ice-sheet accumulation area to drive a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 62 publications
5
46
0
Order By: Relevance
“…These results therefore emphasize the importance of adequate spin-up and assessment of the effects of snowpack spin-up in producing and using SMB in Antarctica. Vandecrux et al (2020b) found that the Fixed version smoothes the firn density profiles, when compared to the dynamical version; this is confirmed by our results. One of the criteria for the dynamical version is that it prefers to merge layers deeper than 5 m of water equivalent, meaning that the top 5 m w.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results therefore emphasize the importance of adequate spin-up and assessment of the effects of snowpack spin-up in producing and using SMB in Antarctica. Vandecrux et al (2020b) found that the Fixed version smoothes the firn density profiles, when compared to the dynamical version; this is confirmed by our results. One of the criteria for the dynamical version is that it prefers to merge layers deeper than 5 m of water equivalent, meaning that the top 5 m w.e.…”
Section: Discussionsupporting
confidence: 90%
“…The second model version uses a Lagrangian framework for the layer evolution developed by Vandecrux et al (2018Vandecrux et al ( , 2020a. Layers evolve through a splitting and merg-4318 N. Hansen et al: Reconciling different drivers of surface mass balance in Antarctica ing dynamic based on a number of weighted criteria.…”
Section: Subsurface Modelmentioning
confidence: 99%
“…While the field observations of preferential percolation depths are limited and from transects much lower in the percolation zone 10,30-32 , breakthrough percolation has been observed in firn as cold as −10°C and around 2 m ahead of the wetting front 10 . Given these observations, firn temperature measurements from the early 2000s at the NASA-SE GCNet site 33,34 and the 2016 GreenTRACS traverse 15,35 suggest that meltwater percolation to depths of up to 2 m during the melt season could be possible on these transects. Altogether, in the central and eastern segments of each transect, the observed densification (0.05-0.1 g cm −3 ) is most consistent with additional refreezing within thin (<0.1 m) layers sometime during the 2013 melt season.…”
Section: Resultsmentioning
confidence: 91%
“…The most recent estimates of Arctic freshwater sources and sinks have been developed by Østerhus et al (2019), Haine et al (2015), Prowse et al (2015), Carmack et al (2016), and Vihma et al (2016). Only Østerhus et al (2019) covers a more recent period through 2015.…”
Section: Changes In Arctic Freshwater Sources and Sinksmentioning
confidence: 99%